Roles of Human Liver Cytochrome P450 Enzymes in Tenatoprazole Metabolism - Thien-Kim Le; Young Jin Park; Gun Su Cha; Fikri A. R. Hardiyanti Oktavia; Dong Hyun Kim; Chul-Ho Yun (MDPI AG, 2022)
Tenatoprazole, a newly developed proton pump inhibitor candidate, was developed as an acid inhibitor for gastric acid hypersecretion disorders such as gastric ulcer and reflux esophagitis. It is known that tenatoprazole is metabolized to three major metabolites of 5'-hydroxy tenatoprazole, tenatoprazole sulfide, and tenatoprazole sulfone in human liver, primarily catalyzed by CYPs 2C19 and 3A4. While CYP2C19 prefers the hydroxylation of tenatoprazole at C-5' position, CYP3A4 is mainly involved in sulfoxidation reaction to make tenatoprazole sulfone. Tenatoprazole sulfide is a major human metabolite of tenatoprazole and is formed spontaneously and non-enzymatically from tenatoprazole. However, its metabolic fate in the human liver is not fully known. Furthermore, no systematic metabolic study has been performed to study tenatoprazole or tenatoprazole sulfide. Here, we studied the functions of human cytochromes P450 in the metabolic pathway of tenatoprazole and tenatoprazole sulfide by using recombinant human P450s and human liver microsomes. Both CYP 2C19 and CYP3A4 showed distinct regioselective and stereospecific monooxygenation activities toward tenatoprazole and tenatoprazole sulfide. Furthermore, a new major metabolite of tenatoprazole sulfide was found, 1'-N-oxy-5'-hydroxytenatoprzole sulfide, which has never been reported. In conclusion, the metabolic fates of tenatoprazole and tenatoprazole sulfide should be considered in the clinical use of tenatoprazole.